Tick-transmitted diseases. Part I. Ixodes ricinus as a reservoir and vector for pathogens - Wójcik-Fatla, Angelina; Szymańska, Jolanta; Buczek, Alicja (Polish Journal of Public Health, 2009)
Ixodes ricinus ticks play the key role as a reservoir and vector for numerous pathogens, including species of medical and epidemiological signifi cance. They are a reservoir and vector of many viruses, bacteria and protozoa. As a result of changes in climate and land use, these parasitic arthropods found new habitats. They are increasingly often observed in cities (parks, private estates, gardens) and industrial areas, where the risk of infecting humans with various pathogens is comparable to that in forest biotopes. Active pastimes, recreation, dog walking in the areas overgrown with bushes or in meadows are conducive to a more frequent contact with ticks. Additionally, an increasing number of tick co-infections with several different pathogens found in recent years, points to a growing probability to infect a host, including a human one, with more than one pathogen.Ixodes ricinus is one of the three-host ticks whose instars, before transforming into the subsequent developmental stage, must feed on the blood of a different host. Mechanisms facilitating infection of the host are: pathogen transfer with the saliva of a feeding tick, regurgitation (a backflow of the intestine contents), excretion of the infected faeces or rubbing the infected secretions in through a broken skin of the host.The paper presents the current knowledge on the occurrence and activity of Ixodes ricinus ticks and their role as a reservoir and vector for pathogenic microorganisms.